Biopolymer-Reinforced Levee for Breach Development Retardation and Enhanced Erosion Control - Dongwoo Ko (Water, 2020)
This study proposes an earthen levee reinforcement method with a new biopolymer-based material to prevent levee scour and breach. It is an eco-friendly method that can efficiently protect the levee slope as it enhances soil strength, even at a very low concentration of biopolymer, and has high resistance to surface runoff in addition to promoting vegetation growth. The function and effectiveness of this method were demonstrated through an overflow-based semi-scale experiment in a previous study. In this study, we examined the effect of biopolymer-mixed soil layer on levee stability against an overflow-induced breach. In these experiments, biopolymer-mixed soils were sprayed on the crest and land-side levee surface. Two full-scale tests were conducted (2.5–2.7 m high and 14 m wide on bottom). Case 1 (control case) consisted of bare sand without any treatment, while Case 2 consisted of a 1.0% biopolymer-mixed soil sprayed on the crest and landside slope of the levee and turf put on it. By applying an image analysis technique, we analyzed the breach phenomenon and breach retardation effect of the levee treated with a biopolymer and covered with vegetation. In this experiment, the slope loss rate of Case 2 was retarded 1.5 to 2.3 times over time as compared to Case 1. During the experiment, we observed that soil erosion followed through the narrow water channel formed by the stripped turfs. This means that the grasses did not root firmly enough to protect the surface. In this regard, although the experimental results may seem unsatisfactory, the biopolymer was found to help improve erosion retardation. In 2020, we will conduct more experiments with different compositions and concentrations of the biopolymer regardless of levee vegetation. With this research, we expect to confirm that the new technology of using biopolymer-treated soils is promising for solving the levee overflow breach problem.